6(b+1)=3

Simple and best practice solution for 6(b+1)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(b+1)=3 equation:


Simplifying
6(b + 1) = 3

Reorder the terms:
6(1 + b) = 3
(1 * 6 + b * 6) = 3
(6 + 6b) = 3

Solving
6 + 6b = 3

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 6b = 3 + -6

Combine like terms: 6 + -6 = 0
0 + 6b = 3 + -6
6b = 3 + -6

Combine like terms: 3 + -6 = -3
6b = -3

Divide each side by '6'.
b = -0.5

Simplifying
b = -0.5

See similar equations:

| 5x+2y+x+y=63 | | 3x-4=7x-44 | | 2y^2+27y-45=0 | | (x^2-x+1)-(2x^2-1)=0 | | 3x-72=-6x+126 | | 1.5x+1.3x=-8 | | 5y+1-y=10+3y+10 | | m+2n=p*n | | f(x)=(x-6) | | 21=4x+3 | | 3.25+0.50x=4.75+0.75x | | f(-x)=4x^2+3x+6 | | 19z=14y-y-3z | | -156=-8+4(-7+6a) | | 6y^2+19y+13=0 | | 3n+g+4n=2 | | (4y-4)+9=29 | | 2x-88=122-8x | | 28=18+x-20 | | (-3+3y)+3=3y | | 13+9x+24=x-3 | | 3(-10t-3)=75 | | y=3.8-2x | | 105-14=s | | 11+4a=1+a+-7a | | -7x-27=8-x-19 | | (3x)+(x-6)=90 | | 4z+z=40-10 | | 2x^2-19x-98=0 | | -6x-4(-2x-7)=40 | | X+x(2.5)=21 | | 3(2x+2)-3=6+3x |

Equations solver categories